Motives and Meanings of Toxic Relationships in Adolescent Interpersonal Relationships in Pontianak City - Devi Tassya Tiara Anggreini; Catur Nugroho (Budapest International Research and Critics University, 2022)
This study focuses on adolescents who are entangled in unhealthy relationships in courtship. A toxic relationship is one in which there is no sense of support for each other. This relationship involves emotional violence, toxic parents, and verbal and nonverbal psychological violence. Therefore, this study discusses the phenomenology of motives & the meaning of toxic relationships to find out what the motives are and how to interpret unhealthy relationships, in this study uses a qualitative method with a phenomenological approach to motives and meanings. The results showed that the form of violence experienced by the informant became a form of verbal and digital violence because the actions taken by their partners were acts of limiting freedom. The informant persists because of the habit of living together, great affection, fear of being alone, and the threat given by his partner.